Teachers’ Efforts to Preserve Classical Pesantren Traditions through a Meaningful Learning Approach - Sulusiyah Sulusiyah; Sugiono Sugiono (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study investigates teachers’ efforts to preserve classical pesantren traditions within meaningful learning in the Religious Program of MAN 1 Probolinggo. Despite the growing influence of digitalization in education, teachers remain committed to maintaining traditional pedagogical practices such as sorogan, bandongan, and kitab kuning study that embody the intellectual legacy of salaf scholars. These practices serve not only as channels for transmitting knowledge but also as frameworks for shaping students’ character, moral discipline, and spiritual awareness. In this process, teachers function as designers of learning experiences who integrate cognitive understanding with emotional and spiritual engagement between teachers, students, and classical texts. This research employs a qualitative approach using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data were obtained through observation, in-depth interviews, and documentation of interactions between teachers and students. The findings show that teachers play a crucial role in sustaining pesantren traditions within formal schooling. Through traditional methods and the cultivation of adab, they create profound, value-oriented, and culturally rooted learning experiences. The study concludes that educational modernization does not rely solely on digital technologies but can also be pursued by revitalizing values, exemplars, and the scholarly heritage of pesantren.